Improved cell growth on additively manufactured Ti64 substrates with varying porosity and nanofibrous coating - Tanzli, Ewin; Kozior, Tomasz; Hajnys, Jiri; Mesicek, Jakub; Brockhagen, Bennet; Grothe, Timo; Ehrmann, Andrea (Heliyon, 2024)
3T3 Swiss albino mouse cells are often used in biotechnological applications. These cells can grow adherently on suitable surfaces. In our study, they were grown on different titanium substrates, comparing commercially available titanium sheets of grade 1 and grade 2, respectively, with Ti64 which was 3D printed with different porosity in order to identify potential substitutes for common well-plates, which could - in case of 3D printed substrates - be produced in various shapes and dimensions and thus broaden the range of substrates for cell growth in biotechnology and tissue engineering. In addition, thin layers of poly(acrylonitrile) (PAN) nanofibers were electrospun on these substrates to add a nanostructure. The common titanium sheets showed lower cell cover factors than common well plates, which could not be improved by the thin nanofibrous coating. However, the Ti sheets with nanofiber mat coatings showed higher cell adhesion and proliferation than pure PAN nanofiber mats. The 3D printed Ti64 substrates prepared by laser metal fusion, on the other hand, enabled significantly higher proliferation of (66 ± 8)% cover factor after three days of cell growth than well plates which are usually applied as the gold standard for cell cultivation ((48 ± 11)% cover factor under identical conditions). Especially the Ti64 samples with higher porosity showed high cell adhesion and proliferation. Our study suggests investigating such porous Ti64 samples further as a potential future optimum for cell adhesion and proliferation.
Keywords: Cell culture; Powder bed fusion; Additive manufacturing; 3T3 cell line; Nanofibers; Laser metal fusion